Teaching Better: A Community College’s Faculty Development Needs - Morris, Adam A.; Miller, Michael T. (Journal of Education and Training, 2023)
Faculty development is a critical area of practice for every higher education institution. Many programs, however, are increasingly designed around assuring institutional compliance rather than equipping faculty to be successful teachers. The current study was designed to explore what a community college’s faculty perceived as important faculty development programming. Using a survey of nearly 400 faculty at a suburban community college, faculty identified programs that focus on linking social technology to academic success, generational differences of students, and addressing student disabilities in the classroom as the most important. Nearly half of responding faculty noted that developmental programing is of high importance to them, and just over a third indicated that programing should be in person rather than online. Findings suggest that faculty are seeking the best possible way to connect with students who have grown up with technology.